2010
DOI: 10.1038/onc.2010.130
|View full text |Cite
|
Sign up to set email alerts
|

Novel alternatively spliced ADAM8 isoforms contribute to the aggressive bone metastatic phenotype of lung cancer

Abstract: ADAMs (a disintegrin and metalloprotease) are transmembrane proteins involved in a variety of physiological processes and tumorigenesis. Recently, ADAM8 has been associated with poor prognosis of lung cancer. However, its contribution to tumorigenesis in the context of lung cancer metastasis remains unknown. Native ADAM8 expression levels were lower in lung cancer cell lines. In contrast, we identified and characterized two novel spliced isoforms encoding truncated proteins, D18a and D14 0 , which were present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…It acts as an active metalloprotease, hydrolyzing myelin basic protein and a variety of peptide substrates based on the cleavage sites of membrane-bound cytokines, growth factors, and receptors [21]. Accumulating evidences have been demonstrated the overexpression of ADAM8 in a variety of human tumors [10][11][12][13][14][15][16]. To our interests on brain malignancies, Wildeboer et al [10] observed maximal ADAM8 mRNA expression in glioblastoma, low-grade oligoastrocytoma, and anaplastic ependymoma.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It acts as an active metalloprotease, hydrolyzing myelin basic protein and a variety of peptide substrates based on the cleavage sites of membrane-bound cytokines, growth factors, and receptors [21]. Accumulating evidences have been demonstrated the overexpression of ADAM8 in a variety of human tumors [10][11][12][13][14][15][16]. To our interests on brain malignancies, Wildeboer et al [10] observed maximal ADAM8 mRNA expression in glioblastoma, low-grade oligoastrocytoma, and anaplastic ependymoma.…”
Section: Discussionmentioning
confidence: 98%
“…Medulloblastoma accounts for nearly 20% of all pediatric tumors in central nervous system and 40% of pediatric posterior fossa tumors [12]. [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, our in vitro co-culture system does not fully reconstitute the complexity of the tumor-bone microenvironment in vivo, where other cells and/or secreted enzymes could potentially contribute to the extracellular proteolytic activity. In this regard, we have recently shown that ADAM8 (a disintegrin and metalloprotease domain) isoforms contribute to the aggressive bone colonization of lung cancer [25]. Moreover the use of a broad-spectrum inhibitor of MMP and ADAM activities markedly attenuates the development of metastatic lesions [12].…”
Section: Discussionmentioning
confidence: 98%
“…Fluorescence was determined using 480/520 nm filter set. Experiment was repeated three times, and each condition was done in sixplicate as described previously [25].…”
Section: Chemotaxis Assaymentioning
confidence: 99%